1999
DOI: 10.1139/z99-148
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dynamics of a migratory wolf population in winter, south-central Ontario (1990-1995)

Abstract: We examined the spatial distribution and movements of migratory wolves (Canis lupus lycaon) to a deer yard located adjacent to Algonquin Provincial Park, Ontario, during 5 winters from 1990 to 1995. Wolves from eastern and central Algonquin Provincial Park followed the annual migration of deer to yards located 13 km outside of the Park boundary. Spatial distributions were determined through mapping of telemetry locations and nearest neighbour analysis. We defined three spacing systems: consistent/high fidelity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In southwest Quebec, Canada, wolves living in areas amid low prey densities had higher adult and pup mortality compared to those living in high prey density areas (Messier 1984), and wolves in Alaska had larger litters in habitats with high levels of ungulate biomass (Boertje and Stephenson 1992). In the absence of alternative prey, we might expect wolves in our study area to make trips more commonly and uniformly to groups of summering elk, despite their remoteness from den sites (see Cook et al 1999). The availability of mule deer as an alternate prey resource may allow wolves the flexibility to respond to seasonal changes in abundance of migratory elk by shifting their diet (Garrott et al 2007) without significantly shifting their distribution.…”
Section: Do Wolves Follow Migratory Prey?mentioning
confidence: 93%
“…In southwest Quebec, Canada, wolves living in areas amid low prey densities had higher adult and pup mortality compared to those living in high prey density areas (Messier 1984), and wolves in Alaska had larger litters in habitats with high levels of ungulate biomass (Boertje and Stephenson 1992). In the absence of alternative prey, we might expect wolves in our study area to make trips more commonly and uniformly to groups of summering elk, despite their remoteness from den sites (see Cook et al 1999). The availability of mule deer as an alternate prey resource may allow wolves the flexibility to respond to seasonal changes in abundance of migratory elk by shifting their diet (Garrott et al 2007) without significantly shifting their distribution.…”
Section: Do Wolves Follow Migratory Prey?mentioning
confidence: 93%
“…), elk {Cervus elaphus), moose (Alces alces) and woodland caribou (Rangifer tarandus caribou) (Young & Goldman 1944;Mech 1970). Studies by Cook et al (1999) and Ballard et al (1997) indicated that some populations or some individuals are migratory in forested regions of North America. However, there have been no studies comparing the genetics of migratory wolves identified directly through telemetry with wolves from populations without migratory prey.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have established that range size and movement patterns of wolves are related to prey availability (density) and distribution, concluding that smaller ranges and increased tolerance to intruders/transients/immigrants result from high prey density and/or diversity, and degree of kinship (Fuller 1989;Cook et al 1999). Average wolf-pack territory sizes vary 14-fold among areas across North America (Fuller et al 2003).…”
Section: Goals and Objectivesmentioning
confidence: 99%
“…Annual range sizes reported for wolves vary between 200 km 2 and >2000 km 2 (Cook et al 1999;Walton et al 2001), depending on density and availability of preferred and alternative prey. Most studies that have concentrated on territorial wolves that prey on ungulates, including deer, elk, moose, and sheep, have concluded that wolves maintain relatively stable annual territories (Walton et al 2001).…”
Section: Movements and Rangesmentioning
confidence: 99%
See 1 more Smart Citation